2022
DOI: 10.3389/fenvs.2022.948016
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Communities’ Risk Assessment and the Effects of Climate Change: A Pathway Toward Green Productivity and Sustainable Development

Abstract: This study was carried out to assess agricultural communities’ understanding of climate change, the adaptation measures being undertaken against climate change, and industrial wastewater irrigation. It was considered important to check agricultural communities’ understanding of climate change, as the majority of the study area belongs to the farming and industry sector. This study was based on primary data collected through a survey in the study area. The results of present study showed that agricultural commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…A broad understanding of facts, ideas, and connections relating to the natural environment and its primary ecosystem is what is meant when someone says they have "environmental knowledge." Researchers have recently discovered that environmental knowledge strengthens the relationship between green human resource management and pro-environmental behaviors (Sohail et al, 2022b;Farrukh, Ansari, Raza, Wu, & Wang, 2022). Researchers believe that people who have a better awareness and knowledge of environmental-related issues are more likely to pick ecofriendly products and technologies (Mustafa et al, 2022b) same is found in the case of electronic vehicles (Mustafa et al, 2021).…”
Section: Moderation Effect Of Environment Knowledgementioning
confidence: 98%
“…A broad understanding of facts, ideas, and connections relating to the natural environment and its primary ecosystem is what is meant when someone says they have "environmental knowledge." Researchers have recently discovered that environmental knowledge strengthens the relationship between green human resource management and pro-environmental behaviors (Sohail et al, 2022b;Farrukh, Ansari, Raza, Wu, & Wang, 2022). Researchers believe that people who have a better awareness and knowledge of environmental-related issues are more likely to pick ecofriendly products and technologies (Mustafa et al, 2022b) same is found in the case of electronic vehicles (Mustafa et al, 2021).…”
Section: Moderation Effect Of Environment Knowledgementioning
confidence: 98%
“…Satisfaction from technology leads to adoption and use of technology or product. Researchers have found that satisfaction from 5G services leads to their adoption in the future (Mustafa et al, 2022d), electronic gadgets (Mustafa et al, 2022a), electronic vehicle adoption (Mustafa et al, 2021), the effect of climate change and adoption techniques to minimize risk (Sohail et al, 2022b), green transportation adoption (Sohail et al, 2021). Furthermore, researchers have revealed that the level of satisfaction experienced by users will have a favorable and substantial influence on their desire to continue using academic library applications (Rafique et al, 2021).…”
Section: Satisfaction and Adoption Intentionmentioning
confidence: 99%
“…The maximum recorded temperature was 45°C, while the wind speed was 94 mph [ 25 ]. Today, Faisalabad is a thriving industrial center with several textile, dye, fertilizer, industrial chemical, pulp and paper, printing, industrial products, and agricultural equipment manufacturers, among others [ 26 ]. Most industrial wastewaters were dumped untreated into the two main drains, Paharang and Madhuana.…”
Section: Methodsmentioning
confidence: 99%